Male partner involvement in birth preparedness, complication readiness and obstetric emergencies in Sub-Saharan Africa: a scoping review - Faye Forbes; Karen Wynter; Berihun M. Zeleke; Jane Fisher (BMC Pregnancy and Childbirth, 2021)
Abstract Background Maternal mortality remains a pressing concern across Sub-Sahara Africa. The ‘Three Delays Model’ suggests that maternal deaths are a consequence of delays in: seeking care, reaching medical care and receiving care. Birth Preparedness and Complication Readiness (BPCR) refers to a plan organised during pregnancy in preparation for a normal birth and in case of complications. Male partners in many Sub-Saharan African communities could play a pivotal role in a woman’s ability to prepare for birth and respond to obstetric complications. This review aimed identify: the extent and quality of research performed on the topic of male partner involvement in BPCR in Sub-Saharan Africa; the degree to which populations and geographic areas are represented; how male partner involvement has been conceptualized; how male partners response to obstetric complications has been conceptualised; how the variation in male partners involvement has been measured and if any interventions have been performed. Methods In this scoping review, articles were identified through a systematic search of databases MEDLINE, EMBASE and Maternity and Infant Care and a manual scan of relevant papers, journals and websites. All authors contributed to the screening process and a quality assessment using the Kmet checklist. The PRISMA checking list for Scoping Reviews was used to guide the search, data charting and reporting of the review The protocol was registered with PROSPERO (ID: CRD42019126263). Results Thirty-five articles met inclusion criteria, reporting: 13 qualitative, 13 cross-sectional, 5 mixed method and 4 intervention studies. Data were contributed by approximately 14,550 participants (numbers were not always reported for focus groups) including: women who were pregnant or who had experienced pregnancy or childbirth within the previous 3 years, their male partners and key informants such as health workers and community leaders. Conclusions The diversity of study designs, aims and source countries in this body of literature reflects an emerging stage of research; as a result, the review yielded strong evidence in some areas and gaps in others. Male partner’s involvement in BPCR and responding to obstetric emergencies can be conceptualised as being centrally involved in responding to complications and having some role in preparing for birth through their position in the chain of decisions and provision of logistic support. However, their knowledge of pregnancy complications and level of preparation for birth is low, suggesting they are making decisions without being fully informed. There is limited evidence on interventions to improve their knowledge. Future research efforts should be focused on producing standardised, culturally appropriate, higher level evidence.